Heterosporicola beijingense sp. nov. (Leptosphaeriaceae, Pleosporales) associated with Chenopodium quinoa leaf spots - Rashika S. BRAHMANAGE; Mei LIU; Dhanushka N. WANASINGHE; Monika C. DAYARATHNE; Li MEI; Rajesh JEEWON; Xinghong LI; Kevin D. HYDE (Phytopathologia Mediterranea, 2020)
A coelomycetous fungus with hyaline, aseptate, oblong to ellipsoidal conidia was isolated from living Chenopodium quinoa leaves with leaf spots, in Beijing, China. Maximum likelihood and Bayesian analyses of a combined LSU, SSU, ITS and TEF sequence dataset confirmed its placement in Heterosporicola in Leptosphaeriaceae. The new taxon resembles other Heterosporicola species, but is phylogenetically distinct, and is introduced as a new species. Heterosporicola beijingense sp. nov. is compared with other Heterosporicola species, and comprehensive descriptions and micrographs are provided.